Access Priorities in Controlling Neonatal Mortality in Iran - Madadzadeh, Negin; Hesam, Somayeh; Yousefi, Setareh (Advances in Nursing & Midwifery, 2024)
Introduction: Despite the success in reducing neonatal mortality in Iran, it is still far from developing countries and some Asian countries in this field. This study seeks to identify access priorities in controlling neonatal mortality for planning. Therefore, factors affecting access can be a predictive factor in controlling neonatal mortality in future macro-level management policies. Methods: This applied cross-sectional research was done by the factor analysis method based on four patterns of reducing neonatal mortality. After reviewing different texts and patterns, the common and non-common dimensions of these patterns were set in a comparative table. The results of comparative studies were designed in the form of a questionnaire and sent to 20 experts for reliability and validity. Validity was confirmed by CVI and CVR methods and reliability by Cronbach’s method. To validate the model, the final questionnaire was completed and collected by interviewing 311 people from seven provinces in a multi-stage interview with the multi-stage random sampling method. Data were analyzed using SPSS25 and AMOS-18 software. Results: A total of six factors were identified as effective in controlling neonatal mortality, which include access to health services, policy-making, health care delivery, health information systems, family participation, and evaluation. Among these, access to health services and evaluation had the highest and the least effects with 23.19% and 1.19% of explained variances, respectively. Conclusions: The availability of a skilled and trained person and the guarantee of the national budget for the availability of these people are the most important factors in access to controlling the mortality rate.